Virus detection via programmable Type III-A CRISPR-Cas systems - Sagar Sridhara (Nature Portfolio, 2021)
CRISPR-Cas based virus detection assays can be both rapid and sensitive. Here the authors use a Type III-A CRISPR-Cas system to detect SARS-CoV-2.